Cognitive Dysfunction in Children of Epileptic Mothers - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Specific cognitive abilities and motor function were investigated at 5½ years in 104 children of epileptic mothers and in 105 control children with normal intelligence at the Child Neurology Department, Children's Castle Hospital, Lastenlinnantie, Helsinki, Finland.